Tumour diameter is not reliable for management of non-secreting pancreatic neuroendocrine tumours. Issue 8 (November 2017) - Mills, Logan; Drymousis, Panagiotis; Vashist, Yogesh; Burdelski, Christoph; Prachalias, Andreas; Srinivasan, Parthi; Menon, Krishna; Cotoi, Corina; Khan, Saboor; Cave, Judith; Armstrong, Thomas; Weickert, Martin O; et al.
Abstract : Small non-functioning pancreatic NETs (pNETs) ≤2 cm can pose a management dilemma in terms of surveillance or resection. There is evidence to suggest that a surveillance approach can be considered since there are no significant radiological changes observed in lesions during long-term follow-up. However, other studies have suggested loco-regional spread can be present in ≤2 cm pNETs. The aim of this study was to characterise the prevalence of malignant features and identify any useful predictive variables in a surgically resected cohort of pNETs. 418 patients with pNETs were identified from 5 NET centres. Of these 227 were included for main analysis of tumour characteristics. Mean age of patients was 57 years, 47% were female. The median follow-up was 48.2 months. Malignant features were identified in 38% of ≤2 cm pNETs. ROC analysis showed that the current cut-off of 20 mm had a sensitivity of 84% for malignancy. The rate of malignant features is in keeping with other surgical series and challenges the belief that small pNETs have a low malignant potential. This study does not support a 20 mm size cut-off as being a solitary safe parameter to exclude malignancy in pNETs.